PENDAMPINGAN PENERAPAN METODE KAUNY DALAM PEMBELAJARAN AL-QURAN PADA LEMBAGA PENDIDIKAN - Shaharoh, Almas Syafa; Irham, Irham; Mulyadi, Acep; Rohayah, Aulia (LPPM Universitas Islam 45, 2024)
The implementation of this community service focuses on increasing the enthusiasm for reading and memorizing the Qur'an through the Qur'an learning process using the Kauny method so that children feel comfortable, happy and relaxed in learning the Qur'an in terms of getting used to reading and then getting used to memorizing the Qur'an. The author conducted two stages of writing methods of socialization and beginner training in the process of learning the Qur'an using the Kauny method. The findings of this study are by applying the Kauny method to TPQ children in Wibawamulya village makes them enthusiastic in memorizing, not easily bored and saturated because of the nature of learning that is not monotonous. And in each lesson there is a story that describes the verse being studied, making it easier for children to imagine and explore the verse and its meaning through movement. This is able to sharpen their brain power in the memorization process.